Synthesis of processible doped polyaniline-polyacrylic acid composites - Gupta B.; Prakash R. (My University, 2025)
Processible composites of emeraldine salt form of polyaniline (PANI) with polyacrylic acid (PAA) are synthesized and studied for their structural, electrical, mechanical, thermal, and electrochemical properties. The processible conducting composites of various weight percentage from 20 wt % to 90 wt % (of PANI) have been prepared by mixing the PANI and PAA under vigorous stirring and sonication conditions. Self-standing films of electroactive homogeneous composites are obtained by solution casting method. A significant improvement in processibility, crystallinity, and thermal stability is observed in the composites; however, the electrical conductivity decreased remarkably as the percentage of PANI is decreased in the composites. The 60 wt % PANI-PAA composite showed crystalline structural property with orthorhombic crystal system and cell parameters as a = 5.93Å, b = 7.57Å, and c = 10.11Å. The 60 wt % PANI-PAA composite also showed better thermal stability and highest capacitance amongst all the composites and used as an active material for development of electrochemical capacitors (parallel plate assembly). The processible composites based electrochemical capacitors using 0.5 M NaClO4-Acetonitril electrolyte showed super capacitance with ease in fabrication and cost effectiveness in comparison to other similar materials based capacitors. © 2009 Wiley Periodicals, Inc.